Trends of illicit arms proliferation in Nigeria and curtailment strategies (2017)
Small arms proliferation has accelerated the rate of crimes, endangering civil security in Nigeria. Terrorism and escalating ethno-religious violent conflicts can also be traced to this trend. The situation which began since the end of the Nigerian civil war appears to have defied efforts to curtail it. The paper rationalised the situation from the frustration-aggression and weak or fragile state theoretical perspectives, it examined the factors that have contributed to the arms proliferation, the dynamics of demand and supply of small arms and the implications of the proliferation on national security and development. Several reasons have been attributed for the trend, including weak regional security’ arrangements in West Africa and porous security borders. Even though there are existing security and legal measures to stop the trend, it appears there is inadequate coordination among existing agencies to stop the trend. The paper suggests that government and the civil society need to demonstrate more commitments to exposing traffickers of small arms and strengthen the relevant agencies to stop their illegal activities